Deuterium trafficking, mitochondrial dysfunction, copper homeostasis, and neurodegenerative disease - Stephanie Seneff; Anthony M. Kyriakopoulos; Anthony M. Kyriakopoulos (Frontiers in Molecular Biosciences)
Deuterium is a natural heavy isotope of hydrogen, containing an extra neutron. Eukaryotic organisms have devised complex metabolic policies that restrict the amount of deuterium reaching the mitochondria, because it damages the ATPase pumps, leading to release of excessive reactive oxygen species and inefficiencies in ATP production. Human metabolism relies heavily on the gut microbiome to assure an abundant supply of deuterium depleted (deupleted) nutrients to the host. Mitochondrial dysfunction is a hallmark of many chronic diseases, and deuterium overload, often due to gut dysbiosis, may be a major factor contributing to this issue. In this paper, we explore the potential role of certain amyloidogenic proteins, including amylin, amyloid beta, the prion protein, huntingtin, and α-synuclein, in disease processes that result in the accumulation of deposits of protein fibrils, along with lipid membrane components of damaged mitochondria, which we argue may be a mechanism to sequester deuterium in order to reduce the deuterium burden in the tissues. We show how cardiolipin, an anionic lipid synthesized in mitochondria and localized to the mitochondrial membrane, may play a central role both in trapping deuterium in the mitochondrial membrane and in inducing protein misfolding to facilitate the formation of deuterium-rich deposits. We focus on the potential role of the amino acid histidine and its interaction with the mineral copper, both to catalyze certain essential reactions and to facilitate the misfolding of amyloidogenic proteins triggered by contact with anionic phospholipids, particularly cardiolipin, and especially in the outer mitochondrial membrane of deuterium-damaged mitochondria.